A reference time scale for Site U1385 (Shackleton Site) on the SW Iberian Margin - Hodell, D.; Lourens, L.; Crowhurst, S.; Konijnendijk, T.; Tjallingii, R.; Jiménez-Espejod, F.; Skinner, L.; Tzedakis, P. C.; Abrantes, Fatima; Acton, Gary D.; Alvarez Zarikian, Carlos A.; Bahr, André; et al. (Global and Planetary Change, 2015)
Variations in sediment color contain very strong precession signals at Site U1385, and the amplitude modulation of these cycles provides a powerful tool for developing an orbitally-tuned age model. We tuned the U1385 record by correlating peaks in L* to the local summer insolation maxima at 37°N. The benthic δ18O record of Site U1385, when placed on the tuned age model, generally agrees with other time scales within their respective chronologic uncertainties. The age model is transferred to down-core data to produce a continuous time series of log(Ca/Ti) that reflect relative changes of biogenic carbonate and detrital sediment. Biogenic carbonate increases during interglacial and interstadial climate states and decreases during glacial and stadial periods. Much of the variance in the log(Ca/Ti) is explained by a linear combination of orbital frequencies (precession, tilt and eccentricity), whereas the residual signal reflects suborbital climate variability. The strong correlation between suborbital log(Ca/Ti) variability and Greenland temperature over the last glacial cycle at Site U1385 suggests that this signal can be used as a proxy for millennial-scale climate variability over the past 1.5 Ma. Millennial climate variability, as expressed by log(Ca/Ti) at Site U1385, was a persistent feature of glacial climates over the past 1.5 Ma, including glacial periods of the early Pleistocene (‘41-kyr world’) when boundary conditions differed significantly from those of the late Pleistocene (‘100-kyr world’). Suborbital variability was suppressed during interglacial stages and enhanced during glacial periods, especially when benthic δ18O surpassed ~ 3.3–3.5‰. Each glacial inception was marked by appearance of strong millennial variability and each deglaciation was preceded by a terminal stadial event. Suborbital variability may be a symptomatic feature of glacial climate or, alternatively, may play a more active role in the inception and/or termination of glacial cycles.